Behavior of double-skin truss-reinforced composite walls under eccentric compression. (May 2023) - Liu, Zhong-Hua; Shu, Gan-Ping; Zhu, Hao; Qin, Ying
Abstract: This paper presented an experimental and theoretical studies on double-skin truss-reinforced composite wall (DSTCW) subjected to eccentric compression. Five full-scale DSTCWs with different loading eccentricities, height-width ratios and truss spacing were conducted under uniaxial eccentric compressive. The effects of those variations on the failure mode, load- axial displacement curve, lateral deflection, strain distribution were discussed. Subsequently, the finite element (FE) models were built and verified to discuss the working mechanism of DSTCWs under eccentric compression, and an extensive parametric analysis was performed to find the vital parameters on the mechanical behavior of DSTCWs subjected to eccentric compression. Finally, based on Eurocode standard EC4, the Interaction model for DSTCW was proposed to estimate the bearing capacity subjected to eccentric compression. The proposed Interaction model was validated against the results from FE model analysis and experiments.